2019
DOI: 10.1111/jog.13957
|View full text |Cite
|
Sign up to set email alerts
|

No impact of treated hyperprolactinemia on cumulative live birth rate and perinatal outcomes in in vitro fertilization‐embryo transfer

Abstract: Aim To investigate whether treated hyperprolactinemia has an impact on pregnancy outcomes in in vitro fertilization/intracytoplasmic sperm injection‐embryo transfer (IVF/ICSI‐ET). Methods A retrospective cohort study was conducted on 535 women who underwent IVF/ICSI‐ET between January 2012 and December 2016, of which 123 had treated hyperprolactinemia (case group), 369 were matched controls. Besides, 43 remained hyperprolactinemic after treatment consisted of abnormal group. Cumulative live birth rate (CLBR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 24 publications
1
13
0
2
Order By: Relevance
“…Our results demonstrated that the average age of women seeking ART was 32 ± 5 years, which is in accordance with findings reported by studies performed locally and internationally [ 18 , 21 ]. They were divided into primary infertility (59%) and secondary infertility (41%), which are also consistent with two other studies that show a higher prevalence of primary infertility [ 18 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results demonstrated that the average age of women seeking ART was 32 ± 5 years, which is in accordance with findings reported by studies performed locally and internationally [ 18 , 21 ]. They were divided into primary infertility (59%) and secondary infertility (41%), which are also consistent with two other studies that show a higher prevalence of primary infertility [ 18 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…The highest incidence of female comorbidities was hypothyroidism (17%), followed by hyperprolactinemia (8%). According to the literature, an early miscarriage can be caused by a decrease in thyroxin levels, and a retrospective cohort study showed non-significant differences in the CLBR between women treated for hyperprolactinemia and control groups [ 21 , 23 ]. These two findings highlight the importance of pre-cycle treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Kamel et al [46] did not find a significant impact of PRL levels (determined by immunoassay) on the prediction of oocyte and embryo quality associated with the fertilization rate. Also, Duan et al [47] did not find differences between control and hyperprolactinemia groups in the reproductive treatment outcomes (retrieved oocytes, MII oocyte rate, and fertilization); however, the authors suggested that hyperprolactinemia may impact endometrial function and implantation, thus lowering the pregnancy rate. Other studies have explored the associations of PRL levels in women during in vitro fertilization treatments, but the relationship with oocyte maturation, fertilization rate, and embryo development remain elusive [48][49][50][51].…”
Section: Is Prolactin a Key Factor During This Process?mentioning
confidence: 96%
“…Τα αντιδραστήρια και τα διαλύματα που χρησιμοποιήθηκαν για τη διεξαγωγή των πειραματικών δοκιμασιών προκειμένου να προσδιορισθεί η συγκέντρωση της ωοθυλακιοτρόπου ορμόνης, της ωχρινοτρόπου ορμόνης, της αντιμυλλέριος ορμόνης, της οιστραδιόλης, της προγεστερόνης και της β-χοριακής γοναδοτροπίνης στον ορό του αίματος των υπογόνιμων γυναικών στη φάση ωοληψίας και εμβρυομεταφοράς κατά τη διάρκεια θεραπείας IVF/ICSI είναι τα ακόλουθα: Σύμφωνα με διαρκώς αυξανόμενες ενδείξεις προκύπτει ότι υπάρχει σχέση μεταξύ α-Αμυλάσης στο σίελο (sAA: saliva A-Amylase) και NA όπως και άλλων δεικτών δραστηριότητας του ΣΝΣ 259,269 . Ύστερα από πρόκληση ψυχολογικού stress σε υγιή άτομα η αύξηση των επιπέδων της NA στον ορό συνοδεύεται από παράλληλη αύξηση της sAA των ατόμων αυτών, υποδεικνύοντας ότι το ένζυμο αυτό μπορεί να αποτελέσει ένα ευαίσθητο μη επεμβατικό ενδιάμεσο βιολογικό δείκτη που αντανακλά τη δραστηριότητα του ΣΝΣ και πιθανώς να επηρεάσει την αναπαραγωγική λειτουργία στον άνθρωπο γεγονός που επιβεβαιώθηκε πρόσφατα σε πειραματόζωα 261,262…”
Section: αντιδραστήρια και διαλύματαunclassified
“…Υπήρξε ο μοναδικός από τους παραπάνω 5 βιολογικούς δείκτες που εμφάνισε διαφορές μεταξύ των δύο ομάδων Α και Β.Πρώιμη έκφραση του δείκτη 'φταρτοποίησης', της προλακτίνης, κατά τη διάρκεια της ωχρινικής φάσης, σχετίστηκε με επανειλημμένες αποτυχίες εμφύτευσης268 . Ωστόσο, δεν υπάρχουν πειστικές ενδείξεις ότι θεραπεία κατά της υπερπρολακτιναιμίας ασκεί οποιαδήποτε θετική επίδραση στο περιγεννητικό αποτέλεσμα και στα ποσοστά γεννήσεων ύστερα από εξωσωματική γονιμοποίηση269 . Στη μελέτη αυτή όντως, σύμφωνα και με προηγούμενες μελέτες270 δεν επιβεβαιώθηκε οποιαδήποτε σχέση μεταξύ επιπέδων προλακτίνης και αποτελεσμάτων θεραπείας IVF/ICSI.…”
unclassified